2022
DOI: 10.3126/kmcj.v4i2.47778
|View full text |Cite
|
Sign up to set email alerts
|

Junk Food Consumption Practices among the College Students in Banke District

Abstract: Junk foods are easy to prepare and take but have low nutritional value and contain only fat, high sugar, salt, calories, and colours which adversely affect the health of college students. The objective of this study was to assess the junk food consumption practice and its causes and study the relationship between socio-demographic factors and frequency of junk food consumption among college students. This study utilized a cross-sectional research design under quantitative research. Three hundred and fifty-four… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…There was association between the types of food consumed and the grade (Class) of the students (p value is 0.000). The study of Sharma (2022) found that all of the respondents consumed junk food. Among them 60.7 percent of the respondents liked to consume junk food at afternoon and 2.8 percent of the respondents like to consume junk food at night.…”
Section: Resultsmentioning
confidence: 99%
“…There was association between the types of food consumed and the grade (Class) of the students (p value is 0.000). The study of Sharma (2022) found that all of the respondents consumed junk food. Among them 60.7 percent of the respondents liked to consume junk food at afternoon and 2.8 percent of the respondents like to consume junk food at night.…”
Section: Resultsmentioning
confidence: 99%
“…These results are like the previous study done and this implies that impulsivity and convenience may be major factors influencing medical students' consumption of fast food. Fast food may seem like a convenient choice for medical students who have limited time for meal preparation due to their busy schedules and rigorous workloads [1]. Furthermore, students' preferences may be influenced and fast food may be more likely to come to mind when thinking about dining options due to its widespread marketing and advertising.…”
Section: Discussionmentioning
confidence: 99%
“…The OCEM Journal of Management, Technology & Social Sciences understanding of the association based on existing knowledge: Food taste can significantly influence motivation for consumption intention on certain foods, including junk foods. The deliciousness and enjoyable taste of junk foods, often high in fat, sugar, and salt, could create a positive sensory experience and increase motivation on junk food among undergraduate students (Sharma, 2022;Sapkota & Neupane, 2018). The PCs were formed through linear combinations of the original variables and were ordered based on the variance they account for within the data.…”
Section: Junk Food Tastementioning
confidence: 99%